2001
DOI: 10.1111/j.1559-1816.2001.tb02655.x
|View full text |Cite
|
Sign up to set email alerts
|

Evil Thoughts But Angelic Actions: Responses to Overweight Job Applicants

Abstract: Quantitative and content analyses were performed to test the hypothesis that the lack-of-fit model (Heilman, 1983) could provide the needed theoretical framework for organizational obesity discrimination. A computer morphing program allowed for the same stimulus applicant to be used in both the average-weight and the overweight conditions. Results of the quantitative analysis show that undergraduate participants perceived overweight (vs. average-weight) applicants as having more negative work-related attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 47 publications
1
49
0
3
Order By: Relevance
“…Previous research has shown various factors such as attractiveness (e.g., Dipboye, Arvey, & Terpstra, 1977;Watkins & Johnston, 2000) or weight (e.g., Pingitore, Dugoni, Tindale, & Spring, 1994;Polinko & Popovich, 2001) can influence the perception of employability. Additionally, the mixed race and sex of the applicants as well as the varying appearance of the headshots, as the headshots were likely taken for different purposes, added further complication to the selection process.…”
Section: Development Of Video Interviewsmentioning
confidence: 99%
“…Previous research has shown various factors such as attractiveness (e.g., Dipboye, Arvey, & Terpstra, 1977;Watkins & Johnston, 2000) or weight (e.g., Pingitore, Dugoni, Tindale, & Spring, 1994;Polinko & Popovich, 2001) can influence the perception of employability. Additionally, the mixed race and sex of the applicants as well as the varying appearance of the headshots, as the headshots were likely taken for different purposes, added further complication to the selection process.…”
Section: Development Of Video Interviewsmentioning
confidence: 99%
“…Although "fit" has potential for explaining discrimination across multiple characteristics, few studies have applied "fit" outside of the sex discrimination literature (e.g., Pichler, Varma, & Bruce, 2010;Polinko & Popovich, 2001). Thus, an important step in establishing the generalizability of the idea of "fit" to explain discrimination is to extend this theory to applicant characteristics other than sex.…”
Section: Stereotypingmentioning
confidence: 99%
“…Research has been conducted in both the lab (e.g., Bellizzi & Hasty, 2001;Brink, 1988;Ding & Stillman, 2005;Larkin & Pines, 1979;Polinko & Popovich, 2001;Rothblum, Miller, & Garbutt, 1988) and in the field (e.g., Averett & Korenman, 1996;Baum & Ford, 2004;Collins & Zebrowitz, 1995;Judge & Cable, 2011;Leigh & Berger, 1989;Morris, 2006;Zhang & Wang, 2004). This research has examined a wide range of criteria, including personality and behavioral dimensions (e.g., Larkin & Pines, 1979), attitudes (e.g., Kennedy & Homant, 1984), hiring decisions (e.g., Larwood, 1995), coworker desirability (e.g., Jasper & Klassen, 1990), income (e.g., Register & Williams, 1990), and employment status (e.g., Tunceli, Li, & Williams, 2006).…”
Section: Sex and Weight Discriminationmentioning
confidence: 99%
See 2 more Smart Citations